UJI EFEKTIVITAS KENTOS KELAPA UNTUK MENINGKATKAN PERTUMBUHAN IKAN SEURUKAN (Osteochilus sp.) - Sholika, Nur; Muliyana, Agusriati; Diana, Farah; Islama, Dini (Universitas Teuku Umar, 2021)
Seurukan fish (Osteocilus sp.) is one of the freshwater fishery commodities that continues to be studied and developed, one of which is by increasing the digestibility of feed through the addition of supplements made from local ingredients such as coconut sprouts in commercial feed and getting the best dose for the growth of seurukan fish (Osteocilus sp.). This study used an experimental method with a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments tested were the use of coconut kentos with doses: P0 (control), P1 (5%/kg), P2 (10%/kg feed) and P3 (15%/kg feed).The results of analysis of variance showed that giving coconut kentos to commercial feed had no significant effect (P>0.05) on growth in weight and length, feed conversion ratio, and survival rate of seurukan fish (Osteochilus sp.). The dose of coconut sprout addition was divided into P0 (control), P1 (5%/kg feed), P2 (10%/kg feed), and P3 (14%/kg feed). The results showed that the dose of P2 (10%/kg feed) resulted in absolute weight growth of 8.63 g, daily length growth rate of 1.18%, conversion ratio feed 2.68% and survival rate 100%.